THE INFLUENCE OF SLEEP HABITS ON COGNITIVE FUNCTIONS IN THE SPEECH OF PRESCHOOL CHILDREN - Pardede, Gabriella; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
This study investigates the influence of sleep habits on the cognitive functions observed in the speech of preschool children. Sleep plays a crucial role in a child’s development, affecting memory, attention, and language skills. The research aims to understand how irregular sleep patterns or insufficient sleep impact the clarity, vocabulary, and structure of preschoolers’ speech. Data were collected from 5 preschool children through parent questionnaires and speech assessments. The findings reveal that children with consistent and adequate sleep show better cognitive abilities, reflected in their ability to form coherent sentences and use varied vocabulary. Conversely, children with poor sleep habits often display difficulties in speech fluency and comprehension. This study highlights the importance of healthy sleep routines for optimal cognitive and language development in early childhood. Recommendations for parents and educators are also provided.